Kombinasi Susu Skim dan Minyak Kelapa yang Dimodifikasi (Modisco) dan Pijat Nafsu Makan dalam Mengoptimalkan Status Gizi Balita Stunting: Combination of Modified Dietetic Skimmed Milk and Coconut Oil (Modisco) and Appetite Massage in Optimizing the Nutritional Status of Stunting Toddlers - Ersila, Wahyu; Fitriyani, Fitriyani; Chabibah, Nur (Universitas Airlangga, 2025)
Background: Improper feeding and appetite disorders are chronically the causes of stunting. Efforts to improve the nutrition of toddlers can be carried out through the provision of additional sources of nutrition. Modified Dietetic Skimmed Milk and Coconut Oil (Modisco) combined with appetite massage is one of the alternatives that need to be tested for effectiveness in optimizing the nutritional status of stunted toddlers. Objectives: This study aimed to determine the effectiveness of the combination of modisco and appetite massage on the nutritional status of stunted toddlers. Methods: The design was quasi-experimental with a pre-test and posttest control design approach. The large sample of 30 stunted children aged 1-5 years was divided into two groups using a simple random sampling technique. The intervention group was given modisco for 15 days and appetite massage 3x/week, and the control group was given only modisco for 15 days. Measurements of weight, height, and nutritional intake before and after the intervention. Data analysis used paired t-tests and independent t-tests. Results: There was a difference in body weight between the intervention and control groups (p-value=0.02; 95%CI=0.28-0.40). There was a difference in nutritional intake in the intervention group and control groups, namely in carbohydrate nutrients (p-value = 0.02; 95%CI=5.67-81.62), Vitamin B1 (p-value≤0.001; 95%CI=-3.97 – (-2, 02)), Vitamin B6 (p-value=0.008; 95%CI=0.17-1.01), Vitamin C (p-value≤0.001; 95%CI=16.01-34.72). There was no significant difference in height/body length of the intervention and control groups (p-value=0.38; 95%CI=-0.03 – (-0.07). Conclusions: The combination of Modisco and appetite massage was more effective in increasing weight and nutritional intake than Modisco alone. Midwives are expected to educate mothers of toddlers to provide Modisco and appetite massage.